Pengembangan Tari Kreasi Berbasis Tema Nusantara untuk Meningkatkan Kreativitas Seni Anak - Lestari, Amanda; Halifah, Syarifah; Palintan, Tien Asmara; Natsir, Tri Ayu Lestari (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
This study employed a Research and Development (R&D) approach aimed at producing a Nusantara-themed creative dance learning medium and examining its feasibility, practicality, and effectiveness in enhancing artistic creativity among early childhood learners at TK Kartika XX-12 Kota Parepare. The developed product was a creative dance video entitled “Wonderland Indonesia”, designed by integrating elements of movement, music, expression, and visual presentation based on Nusantara cultural values and tailored to the characteristics of Group B children. The development process followed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were 11 children from Group B. Data were collected through observation, interviews, questionnaires, and tests. Data analysis included expert validation by media and content specialists, analysis of teacher responses, and effectiveness testing using the N-Gain formula based on pretest and posttest results of children’s artistic creativity. The findings indicate that the developed creative dance video was categorized as valid to highly valid according to expert assessments and received very positive responses from teachers. The effectiveness test yielded an N-Gain score of 0.87, classified as high, indicating a significant improvement in children’s artistic creativity, particularly in terms of fluency, flexibility, originality, and elaboration. Therefore, the Nusantara-themed creative dance video is proven to be feasible, practical, and effective as an arts learning medium for enhancing artistic creativity in early childhood education.